Wounds morphologic assessment: application and reproducibility of a virtual measuring system, pilot study - Guarro, Giuseppe; Cozzani, Federico; Rossini, Matteo; Bonati, Elena; Del Rio, Paolo (Acta Biomedica Atenei Parmensis, 2021)
Background and Aims. Assessment of wounds morphology can be considered, in the everyday medical activity, the first step for the correct pathway of diagnosis. Authors present a pilot study focused on the statistical analysis of 32 cases of wounds measurements conducted by both the traditional method (paper ruler) both the digital smartphone analysis. Materials and Methods.32 lesions were morphologically evaluated. All the enrolled patients were evaluated by both the traditional method (paper ruler) both a digital smartphone analysis based on the app imitoMeasure. The extracted data were compared to the traditional measurements and a statistical analysis was based on intraclass correlation coefficients (ICC). Results. Three morphological parameters were evaluated: width (expressed in cm), length (expressed in cm) and area (expressed in cm2). The area (expressed in cm2) was found to be the less comparable, but the data were close in this case, too. Conclusion.The present study shows that the digital measuring systems should be easily addressed as versatile tools that could be applied in daily clinical practice in the future.